Prostate Cancer: Community Education and Disparities in Diagnosis and Treatment - Carthon, Bradley; Sibold, Hannah C.; Blee, Shannon; D. Pentz, Rebecca (The oncologist (Dayton, Ohio), 2021)
Prostate cancer remains the leading diagnosed cancer and the second leading cause of death among American men. Despite improvements in screening modalities, diagnostics, and treatment, disparities exist among Black men in this country. The primary objective of this systematic review is to describe the reported disparities in screening, diagnostics, and treatments as well as efforts to alleviate these disparities through community and educational outreach efforts. Critical review took place of retrospective, prospective, and socially descriptive data of English language publications in the PubMed database. Despite more advanced presentation, lower rates of screening and diagnostic procedures, and low rates of trial inclusion, subanalyses have shown that various modalities of therapy are quite effective in Black populations. Moreover, patients treated on prospective clinical trials and within equal‐access care environments have shown similar outcomes regardless of race. Additional prospective studies and enhanced participation in screening, diagnostic and genetic testing, clinical trials, and community‐based educational endeavors are important to ensure equitable progress in prostate cancer for all patients. Implications for Practice Notable progress has been made with therapeutic advances for prostate cancer, but racial disparities continue to exist. Differing rates in screening and utility in diagnostic procedures play a role in these disparities. Black patients often present with more advanced disease, higher prostate‐specific antigen, and other adverse factors, but outcomes can be attenuated in trials or in equal‐access care environments. Recent data have shown that multiple modalities of therapy are quite effective in Black populations. Novel and bold hypotheses to increase inclusion in clinical trial, enhance decentralized trial efforts, and enact successful models of patient navigation and community partnership are vital to ensure continued progress in prostate cancer disparities. Traditionally, Black men with prostate cancer have had higher incidence and lower rates of survival. This article addresses barriers in screening, diagnosis, treatment, and community education that contribute to the disparate burden of prostate cancer among multiple populations and highlights innovative ways that new developments and advances can be more broadly disseminated and used for all patients with prostate cancer.